CONTROL INTERNO Y OBLIGACIONES TRIBUTARIAS EN LA EMPRESA AGURTO & MORVELI E HIJOS S.A.C, 2017 - ESTRELLA PAUCAR, LIZ (2018)
The general objective of the investigation is to determine the relationship of internal control and tax obligations in the company AgurtoMorveli e Hijos SAC, 2017. The hypotheses with which it was operationalized are as follows: Internal control if it has a considerable relationship with the tax obligations in the Agurto&Morveli e Hijos SAC Company 2017. The methodology used was correlational. The subjects of the sample constituted the workers of the company Agurto&Morveli e Hijos S.A.C. The most important results of the investigative process are:Agurto&Morveli e Hijos S.A.C. It does not have a good internal control management. The main conclusions reached are: the company Agurto&Morveli e Hijos S.A.C. they do not have good internal control, and the absence is reflected in the breach of tax obligations and because there is tax evasion, they are incurring infractions and tax penalties that will harm the company. In addition, it may be noted that the aforementioned work serves as a precedent for future research because a solution has been provided that will serve researchers or workers in the business world.